Characterization of a dual-action adulticidal and larvicidal interfering RNA pesticide targeting the Shaker gene of multiple disease vector mosquitoes. - Keshava Mysore; Limb K Hapairai; Longhua Sun; Ping Li; Chien-Wei Wang; Nicholas D Scheel; Alexandra Lesnik; Jessica Igiede; Max P Scheel; Na Wei; David W Severson; Molly Duman-Scheel (Public Library of Science (PLoS), 2020)
The existing mosquito pesticide repertoire faces great challenges to sustainability, and new classes of pesticides are vitally needed to address established and emerging mosquito-borne infectious diseases. RNA interference- (RNAi-) based pesticides are emerging as a promising new biorational mosquito control strategy. In this investigation, we describe characterization of an interfering RNA pesticide (IRP) corresponding to the mosquito Shaker (Sh) gene, which encodes an evolutionarily conserved voltage-gated potassium channel subunit. Delivery of the IRP to Aedes aegypti adult mosquitoes in the form of siRNA that was injected or provided as an attractive toxic sugar bait (ATSB) led to Sh gene silencing that resulted in severe neural and behavioral defects and high levels of adult mortality. Likewise, when provided to A. aegypti larvae in the form of short hairpin RNA (shRNA) expressed in Saccharomyces cerevisiae (baker's yeast) that had been formulated into a dried inactivated yeast tablet, the yeast IRP induced neural defects and larval death. Although the Sh IRP lacks a known target site in humans or other non-target organisms, conservation of the target site in the Sh genes of multiple mosquito species suggested that it may function as a biorational broad-range mosquito insecticide. In support of this, the Sh IRP induced both adult and larval mortality in treated Aedes albopictus, Anopheles gambiae, and Culex quinquefasciatus mosquitoes, but was not toxic to non-target arthropods. These studies indicated that IRPs targeting Sh could one day be used in integrated biorational mosquito control programs for the prevention of multiple mosquito-borne illnesses. The results of this investigation also suggest that the species-specificity of ATSB technology, a new paradigm for vector control, could be enhanced through the use of RNAi-based pesticides.